2016
DOI: 10.1002/ijc.30171
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of acid ceramidase inhibitor LCL521 with tumor response to photodynamic therapy and photodynamic therapy‐generated vaccine

Abstract: Acid ceramidase has been identified as a promising target for cancer therapy. One of its most effective inhibitors, LCL521, was examined as adjuvant to photodynamic therapy (PDT) using mouse squamous cell carcinoma SCCVII model of head and neck cancer. Lethal effects of PDT, assessed by colony forming ability of in vitro treated SCCVII cells, were greatly enhanced when combined with 10 µM LCL521 treatment particularly when preceding PDT. When PDT-treated SCCVII cells are used to vaccinate SCCVII tumor-bearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…It should be also mentioned that in this paper the granulocytic Mregs have not been characterized with respect to their cytokine profile and other functional attributes. Recently, we have reported on another interesting agent, acid ceramidase inhibitor LCL521, which inhibits the engagement of both Tregs and Mregs and acts as an effective adjuvant to PDT vaccines [30]. …”
Section: Resultsmentioning
confidence: 99%
“…It should be also mentioned that in this paper the granulocytic Mregs have not been characterized with respect to their cytokine profile and other functional attributes. Recently, we have reported on another interesting agent, acid ceramidase inhibitor LCL521, which inhibits the engagement of both Tregs and Mregs and acts as an effective adjuvant to PDT vaccines [30]. …”
Section: Resultsmentioning
confidence: 99%
“…LCL521 was shown to be the most active toward AC and to prevent relapse of prostate cancer in mice 72 . LCL521 also improved the efficacy of photodynamic therapy in head and neck cancer 73 . As described above, ceramide analog LCL204 was shown to decrease AC activity and induce ceramide-mediated apoptosis of AML cell lines and patient samples as well as significantly extend the life of AML engrafted mice 27 .…”
Section: Ac Inhibitorsmentioning
confidence: 98%
“…Hence, developing acid ceramidase inhibitors such as LCL521 have been studied as a possible immunosuppressive agent . The use of LCL521 in combination with PDT studied by Korbelik et al suppressed Treg cells and myeloid derived suppressor cells (MDSCs) populations in the tumor draining lymph node compared to standard PDT treatment as analyzed by flow cytometry . The suppression however, was not seen in spleen and this critical observation suggested that application of LCL521 allowed PDT to realize its full immunostimulatory potential in recruitment of macrophages and CD8 + cytotoxic T cells .…”
Section: Pdt Cancer Immunotherapymentioning
confidence: 99%
“…The use of LCL521 in combination with PDT studied by Korbelik et al suppressed Treg cells and myeloid derived suppressor cells (MDSCs) populations in the tumor draining lymph node compared to standard PDT treatment as analyzed by flow cytometry . The suppression however, was not seen in spleen and this critical observation suggested that application of LCL521 allowed PDT to realize its full immunostimulatory potential in recruitment of macrophages and CD8 + cytotoxic T cells . It is well known that Treg cells strongly dampen the immune activation which make them a significant target in cancer immunotherapy .…”
Section: Pdt Cancer Immunotherapymentioning
confidence: 99%